PENGARUH POLA PENGGERGAJIAN TERHADAP RENDEMEN DAN WAKTU MENGGERGAJI KAYU MERANTI (SHOREA SPP.) *) - Osly Rachman; Sadan Widarmana; Surjono Surjokusumo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The effects of sawing pattern on recovery and sawing time was studied using 72 logs of meranti (Shorea spp.). The logs were divided into 4 grades i.e., Prime, First, Second and Local, each group consisting of 18 logs. Each group was sawn with 3 different sawing patterns, namely semi quarter, round and live sawing. In the sawing pattern study the effect of logs diameter, brittle heart, and sapwood on recovery were also observed.The results indicated that semi quarter, round, and live sawing patterns generated a recovery as much as 46,37 %, 43,48 % and 37,61 %, respectively. The recovery of Prime grade logs was 46,92 % which was not significantly different from that of the First grade logs. The Second grade logs produced a recovery of 37.12 % and was not significantly different from that obtained from Lokal grade logs. The sawing rate was highest when live sawing pattern was applied, i.e., 0.92 m3/ hour.